Aberrant intrinsic functional connectivity within and between corticostriatal and temporal–parietal networks in adults and youth with bipolar disorder. Issue 7 (29th February 2016) - Stoddard, J.; Gotts, S. J.; Brotman, M. A.; Lever, S.; Hsu, D.; Zarate, C.; Ernst, M.; Pine, D. S.; Leibenluft, E.
Abstract : Background: Major questions remain regarding the dysfunctional neural circuitry underlying the pathophysiology of bipolar disorder (BD) in both youths and adults. In both age groups, studies implicate abnormal intrinsic functional connectivity among prefrontal, limbic and striatal areas. Method: We collected resting-state functional magnetic resonance imaging (fMRI) data from youths and adults (ages 10–50 years) with BD ( n = 39) and healthy volunteers (HV; n = 78). We identified brain regions with aberrant intrinsic functional connectivity in BD by first comparing voxel-wise mean global connectivity and then conducting correlation analyses. We used k-means clustering and multidimensional scaling to organize all detected regions into networks. Results: Across the brain, we detected areas of dysconnectivity in both youths and adults with BD relative to HV. There were no significant age-group × diagnosis interactions. When organized by interregional connectivity, the areas of dysconnectivity in patients with BD comprised two networks: one of temporal and parietal areas involved in late stages of visual processing, and one of corticostriatal areas involved in attention, cognitive control and response generation. Conclusions: These data suggest that two networks show abnormal intrinsic functional connectivity in BD. Regions in these networks have been implicated previously in BD. We observed similar dysconnectivity in youths and adults with BD. These findings provide guidance for refining models of network-based dysfunction in BD.